When is birthweight at term abnormally low? A systematic review and meta‐analysis of the association and predictive ability of current birthweight standards for neonatal outcomes. (8th January 2014) - Malin, GL; Morris, RK; Riley, R; Teune, MJ; Khan, KS
<x xml:space="preserve">Abstract</x> Background Intrauterine growth restriction is a cause of neonatal morbidity and mortality. A variety of definitions of low birthweight are used in clinical practice, with a lack of consensus regarding which definitions best predict adverse outcomes. Objectives To evaluate the relationship between birthweight standards and neonatal outcome in term‐born infants (at ≥ 37 weeks of gestation). Search strategy MEDLINE (1966–January 2011), EMBASE (1980–January 2011), and the Cochrane Library (2011:1) and MEDION were included in our search. Selection criteria Studies comprising live term‐born infants (gestation ≥ 37 completed weeks), with weight or other anthropometric measurements recorded at birth along with neonatal outcomes. Data collection and analysis Data were extracted to populate 2 × 2 tables relating birthweight standard with outcome, and meta‐analysis was performed where possible. Main results Twenty‐nine studies including 21 034 114 neonates were selected. Absolute birthweight was strongly associated with mortality, with birthweight < 1.5 kg giving the largest association (OR 48.6, 95% CI 28.62–82.53). When using centile charts, regardless of threshold, the summary odds ratios were significant but closer to 1 than when using absolute birthweight. For all tests, summary predictive ability comprised high specificity and positive likelihood ratio for neonatal death, but low sensitivity and a negative likelihood ratio close to 1. Author's conclusions Absolute birthweight is a prognostic factor for neonatal mortality. The indirect evidence suggests that centile charts or other definitions of low birthweight are not as strongly associated with mortality as the absolute birthweight. Further research is required to improve predictive accuracy.